Utility of the Smart App Creator Application as an Arabic Learning Media - Yelfi Dewi S; Amrina Amrina; Gazali Gazali; Adam Mudinillah; Annisa Agustina; Yovan Luksfinanto (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
The difficulty of practical media makes educators not innovate in the learning process, especially in delivering subject matter. Even though the technology is beneficial for this, one of which is the Smart App Creator application. Smart App Creator is very easy to use by educators because this application is a user interface; easy to understand. This research was conducted to determine the benefits of a Smart App Creator software in making learning media. This research method was qualitative with a library model; analyzed national and international journals and interview models; interviewed three teachers and nine students at different Islamic junior high schools. The results of this study explained that learning media designed using Smart App Creator software can provide motivation and foster enthusiasm for learning of students because this software contains elements of text, audio, video, and animation that are combined in one media; what's interesting is that this application can be opened. On a laptop or computer without installing the main application and can also be installed on an Android smartphone and has the advantage of not being connected to the Internet.